Fabrication, structure, electrochemical properties and lithium-ion storage performance of Nd:BiVO4 nanocrystals. Issue 3 (15th February 2020) - Xie, Ruishi; Li, Yuanli; Huang, Heyan; Su, Li; Li, Ling; Pan, Xiaoqin; Guo, Zhiyuan; Luo, Fen; Guo, Zhicheng; Guo, Baogang; Chi, Fangting; Ma, Yongjun; et al.
Abstract: Nd:BiVO4 nanocrystals were synthesized by an effective and simple approach. Nd was incorporated into BiVO4 host to enhance electronic conductivity and lithium-ion diffusion kinetics, thus promoting the electrochemical performance. When employed as anode materials in lithium-ion batteries, a good cycling stability and high capacity of ~611 mAh g −1 at 100 mA g −1 were delivered. The work can be extensively employed for fabricating other electrode materials and promoting the electrochemical performance in energy storage correlative domains.